Thermofluid modeling for energy efficiency applications - Khan, M. M. K.; Hassan, N. M. S. (London, UK : Academic Press, 2015)
Thermofluid Modeling for Sustainable Energy Applications provides a collection of the most recent, cutting-edge developments in the application of fluid mechanics modeling to energy systems and energy efficient technology. Each chapter introduces relevant theories alongside detailed, real-life case studies that demonstrate the value of thermofluid modeling and simulation as an integral part of the engineering process. Research problems and modeling solutions across a range of energy efficiency scenarios are presented by experts, helping users build a sustainable engineering knowledge base. The text offers novel examples of the use of computation fluid dynamics in relation to hot topics, including passive air cooling and thermal storage. It is a valuable resource for academics, engineers, and students undertaking research in thermal engineering.
Includes index.
Title details screen (ScienceDirect, viewed September 9, 2015).
Elsevier
Keywords: Computational fluid dynamics; Computational fluid dynamics; Electronic books